Essai de classement typo-technologique des araires à partir des pièces métalliques découvertes en Gaule romaine en vue de leur reconstitution - André Marbach (Revue Archéologique du Centre de la France)
Metallic pieces of tilling implements from Roman Gaul, are practically the only archaeological elements at our disposal to reconstruct the tools. Authors such as S.E. Rees (GB), R. Pohanka (Austria), and above all J. Henning (South East of Europe) have made proposals concerning the reconstruction of tilling implements of that period. What is to be thought of these positions? A method of research has been developed from a fine analysis of the metallic pieces listed in a catalogue of these pieces for Gaul. The shares have been classified according to their working surface, the form of their sockets and the angle of the wearing surface with the ground if it is observable. As for the tanged shares the filing is similar, the length of the tang has however been taken into account here. From the values known for these pieces and a technical study with modelisation of the tilling implement, the possibility of a reconstruction of the ard has been explored. Researchers are here reminded of how important it is to publish the description of the pieces found with the utmost precision for the drawing as well as for the dimensions. As far as ards fitted with a socket share are concerned uncertainty prevails except for shares with a small working surface which, generally, are single ards (manche-sep). The reconstruction of tanged share-ards seems possible including the length of the draught-beam (chambige). Several concrete examples of reconstructed ards have been studied. Thus, if the reconstruction of a tanged share from metallic pieces, tang and coulter may be envisaged, that of iron share ards is uncertain except for plough-ards (reversible).